2019
DOI: 10.3889/oamjms.2019.850
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of In Situ Cross-Linked N-Maleoyl Chitosan-Oxidized Sodium Alginate Hydrogels for Drug Delivery Applications

Abstract: AIM: This study was aimed to prepare in situ cross-linked N-maleoyl chitosan – oxidised sodium alginate (MCS – OSA) hydrogel loaded with metronidazole (MTZ) for drug delivery applications. METHODS: The hydrogel was prepared by in situ cross-linking via Schiff base reaction between amine (-NH2) groups from MCS and aldehyde (-CHO) groups from OSA at the different ratio, and the MTZ was loaded into the hydrogels along with the gelatin processes. RESULTS: The highest drug entrapment efficiency (DEE) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This peak was attributed to the C�O stretching vibration of the aldehyde functional group of OSA and also demonstrated that NaIO 4 had converted the adjacent hydroxyl groups at the C-2 and C-3 positions on the SA backbone to the aldehyde groups. 15,20 Not only that, we further confirmed the successful preparation of HACC and OSA by 1…”
Section: Synthesis and Characterization Of The Hacc And Osasupporting
confidence: 71%
See 2 more Smart Citations
“…This peak was attributed to the C�O stretching vibration of the aldehyde functional group of OSA and also demonstrated that NaIO 4 had converted the adjacent hydroxyl groups at the C-2 and C-3 positions on the SA backbone to the aldehyde groups. 15,20 Not only that, we further confirmed the successful preparation of HACC and OSA by 1…”
Section: Synthesis and Characterization Of The Hacc And Osasupporting
confidence: 71%
“…For example, Wang et al constructed an injectable, bioresponsive, and self-healing hydrogel based on OSA and hydrazide-modified poly­(ethylene glycol) (PEG), formed by Schiff base reaction with good injectability . What’s more, previous studies on OSA-based composite hydrogels have shown that combining OSA with other polymers can provide superior performance, including excellent biocompatibility, controlled biodegradability, and better reactivity, and can be quality-metabolized. However, the current series of hydrogels prepared based on OSA still have certain defects, such as significantly weaker cross-linking of divalent ions, uncontrollable cross-linking reactions, and very weak mechanical strength . OSA as an anionic polymer, the molecular chain not only includes residues of carboxyl and hydroxyl groups that can form polyelectrolyte complexes with polycations (such as poly- l -lysine, CS) but also contains oxidized aldehyde groups that can cross-link with polymers with amino groups by Schiff base self-cross-linking, thus improving the cross-linked reaction to improve the mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] When used in drug delivery, the exchange of inner and outer substances in the gel network can be conveniently altered by changing the gel structure. 18,19,[28][29][30][31][32] Previously, we reported that adding polycations into a nanogel improved the releasing rate of cation drugs, and these composite gels have improved disease control. 33 Theoretically, adding polycations into metal nanoparticle composite nanogels would also increase the releasing rate of cation molecules or ions in the gels.…”
Section: Introductionmentioning
confidence: 99%
“…The rich functional groups of polysaccharide molecules facilitate the design and modification of bio‐based nanogels, making them highly practical for many applications 25–27 . When used in drug delivery, the exchange of inner and outer substances in the gel network can be conveniently altered by changing the gel structure 18,19,28–32 . Previously, we reported that adding polycations into a nanogel improved the releasing rate of cation drugs, and these composite gels have improved disease control 33 .…”
Section: Introductionmentioning
confidence: 99%